PERAN BENDA ASLI (REAL OBJECT) DAN PEMANFAATANNYA DALAM PROSES PEMBELA.JARAN DI SEKOLAH DASAn - Sungkono, Sungkono (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Study in elementary school would be effective if instructional material discussion takes place concretely, remembers the cognitive development of elementary school student stays at concrete level. Presentation of instructional material will have concrete characteristic when the study using or exploits real object. Real object can be classified in two that is object and specimen. Real object has vital importance role in study activity at elementary school. The role seems lo starling ji-om pre-study activity that is stimulating and motivates student in following lesson; al study core activity, original object ha.i role that is assisting to watch over attention and grows active activity; and the role of utilization real object al follow-up study activity, student would more free lo do enrichment material which has been studied Utilization of real object in study ac:ivily can be through in two techniques that are bringing class to external world and brings world into class. So the utilization can run effective, ejpecially teacher need to go through phases and utilization stages oft he real object.